Truth, Lies, and Morality in the Character of Charles Cullen as Reflected in Good Nurse (2022) - Muchamad Husnil Irsad; Abdur Rofik (Metaphor, 2024)
This study is aimed to analyse: 1. The deconstruction concept of Truth of healthcare This study is aimed to analyse: 1. To explain the deconstruction concept of Truth as reflected in The Good Nurse (2022), 2. To explain The deconstruction concept of Lies as reflected in The Good Nurse (2022),3. To explain The deconstruction concept of Morality as reflected in The Good Nurse (2022). The researcher used a qualitative method to examine the problem. The object of this research is the character of Charles Cullen in the movie The Good Nurse (2022). The data used in this study were collected by the researcher through several steps, namely watching and reading, identifying, classifying, and selecting. In order to answer the problem formulation and draw conclusions from this research, the data that has been selected is then analyzed by the researcher through several steps, namely displaying, explaining, and interpreting. The approaches and theories that researchers use to analyze the problem are deconstruction theory and the concept of Truth, the concept of Lies, and the concept of Morality. The results of this study show that (1) deconstruction. truth reveals that Charles Cullen, despite appearing to be a good and professional nurse, is actually a serial killer. (2) The deconstruction of lies in this movie reveals how lies can be personal and institutional. (3) The deconstruction of morality in The Good Nurse (2022) reveals the complex moral conflicts in the world of healthcare, questioning our view of right and wrong in the healthcare profession.